Changes in Intra-Amniotic, Fetal Intrathoracic, and Intraperitoneal Pressures with Uterine Contraction: A Report of Three Cases - Daisuke Katsura; Yuichiro Takahashi; Shigenori Iwagaki; Rika Chiaki; Kazuhiko Asai; Masako Koike; Shunsuke Yasumi; Madoka Furuhashi (Hindawi Limited, 2018)
Intra-amniotic, fetal intrathoracic, and intraperitoneal pressures during pregnancy have been previously investigated. However, to our knowledge, changes in these pressures during uterine contractions have not been reported. Herein, we present three cases of polyhydramnios, fetal pleural effusion, and fetal ascites, in which intra-amniotic, fetal intrathoracic, intraperitoneal pressures increased with uterine contractions. These pressure increases may affect the fetal circulation. We suggest that managing potential premature delivery (e.g., with tocolysis) is important in cases with polyhydramnios and excess fluid in fetal body areas, such as the thorax, abdomen, and heart. The results of this preliminary study on intrafetal pressure measurements will be useful in performing fetal and neonatal surgeries in the future.